2020
DOI: 10.1126/scitranslmed.aba5464
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 signals converge in a lymphoid–dendritic cell pathway that promotes anticancer immunity

Abstract: Tumor-infiltrating dendritic cells (DCs) correlate with effective anticancer immunity and improved responsiveness to anti–PD-1 checkpoint immunotherapy. However, the drivers of DC expansion and intratumoral accumulation are ill-defined. We found that interleukin-2 (IL-2) stimulated DC formation through innate and adaptive lymphoid cells in mice and humans, and this increase in DCs improved anticancer immunity. Administration of IL-2 to humans within a clinical trial and of IL-2 receptor (IL-2R)–biased IL-2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 74 publications
5
51
2
Order By: Relevance
“…A Tγδ17-MDSC immunosuppressive axis had been previously identified in human colorectal carcinoma, 43 which could be disrupted by IL-2c treatment based on our data. Further, RAG1 KO mice have functional innate lymphoid cells that contributed to IL-2c efficacy against subcutaneous B16 melanoma challenge, 12 whereas IL-2c did not treat subcutaneous MB49 in these studies, further supporting tissue- and/or tumor-specific IL-2c effects requiring additional investigations.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…A Tγδ17-MDSC immunosuppressive axis had been previously identified in human colorectal carcinoma, 43 which could be disrupted by IL-2c treatment based on our data. Further, RAG1 KO mice have functional innate lymphoid cells that contributed to IL-2c efficacy against subcutaneous B16 melanoma challenge, 12 whereas IL-2c did not treat subcutaneous MB49 in these studies, further supporting tissue- and/or tumor-specific IL-2c effects requiring additional investigations.…”
Section: Discussionmentioning
confidence: 76%
“… 43 Interestingly, we found that IL-2c reduced the frequency ( figure 6D ) and number ( figure 6E ) of bladder TNF-α + Vγ4δ4 cells, with a concomitant reduction in PMN-MDSC frequency ( figure 6F ). Intratumoral monocytic MDSC (M-MDSC) content was unchanged by IL-2c ( online supplemental figure S4E ), suggesting that IL-2c treatment could include a specific reduction of PMN-MDSCs, possibly via IL-17 or TNF-α effects that could include IL-2c-induced TNF-α production by innate lymphoid cells recently described in a subcutaneous melanoma model, 12 an area requiring further investigation.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, accumulated evidence suggests that IL2 signaling in the TME favors responsiveness to PD1 blockade. [70][71][72][73] As shown in figure 7H,I, skin immunization resulted in the recruitment of increased levels of IL2 + CD4 + TIL in the tumor core, which may at least partially explain the ability of skin immunization to convert PD1-resistant tumors into αPD1responsive tumors (figures 2A and 4D).…”
Section: Skin Immunization Improves Therapeutic Efficacy Over DC Cellmentioning
confidence: 99%